Effect of Spray Solution Recirculation on the Sprayer, Caused by Pumping, on the Droplet Spectra Generated When Spraying Different Solutions - Antuniassi, Ulisses R. [UNESP]; Mota, Alisson A.B.; Chechetto, Rodolfo G.; Carvalho, Fernando K.; Ovejero, Ramiro F.L.; Barbosa, Henrique N.; Palhano, Matheus G.; De Araujo, Vitor C.R. [UNESP] (ASTM International, 2022)
The aim of this work was to evaluate the effect of spray solution recirculation on the sprayer, caused by pumping, on the droplet spectra generated when spraying different solutions. A sprayer built to operate with piston or centrifugal pumps was used to simulate different intensities of pumping recirculation, providing 300 kPa to a nozzle inside a spray chamber, where the droplet spectra generated over time were measured by a VisiSize P15 particle analyzer (Oxford Lasers, UK). The volume median diameter (VMD), the percentage by volume composed of droplets smaller than 150 μm (V150), and the relative span (RS) were calculated for TTI 11003 (Spraying Systems Co.) spraying tank mixtures of dicamba and glyphosate: 2.0 L c.p./ha of a formulation of dicamba diglycolamine salt (480 g a.e./L) and 3.0 L c.p./ha of a formulation of glyphosate potassium salt (480 g a.e./L). Four spray solutions were prepared: herbicides alone and mixed with adjuvants based on three technologies: guar gum (0.75% v/v), polymer (0.6% v/v), and methylated seed oil (0.1% v/v). All solutions received 0.5% v/v of a volatility reduction adjuvant. Three recirculation levels were considered: 1.0 to 2.5 cycles, 4.0 to 6.9 cycles, and 16 to 20 cycles (one cycle means that the solution passed through the pump once). The results showed that the polymer adjuvant was more sensitive to the shear caused by recirculation, providing droplet spectra more prone to drift. Other adjuvants had less or no significant interference on their performance after being pumped. Differences between pump types depended on the type of adjuvant.
Keywords: adjuvant; dicamba; drift; formulation; glyphosate; guar gum; Herbicides; spray solutions; sprayer pump; weeds